Exposing WPA2 security protocol vulnerabilities. (1st January 2014) - Tsitroulis, Achilleas; Lampoudis, Dimitris; Tsekleves, Emmanuel
Wi-Fi protected access 2 (WPA2) is considered one of the most secure protocols employed in wireless local area networks (WLANs). This is despite of having significant security vulnerabilities. The aim of this paper is two-fold. Firstly it analyses the WPA2 security protocol and presents its weaknesses in detail. Secondly it presents a methodology that demonstrates how the WPA2 security protocol can be fully exposed by malicious attacks. Importantly, proposals on how to enhance its security are offered.